FAKTOR KEMAMPUAN, DISIPLIN DAN MOTIVASI DALAM PENGARUHNYA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN TANETE RILAU KABUPATEN BARRU - Askar Askar (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
This study aimed to obtain information on work ability, work discipline and motivation of employees working Tanete Rilau District Office District Barru.Metode used in this study is the method of multiple linear regression. The test results showed using multiple linear regression analysis variables work ability, work discipline and motivation to work as much influence on the performance of 44.7% while the remaining 55.3% outside the influence of this research model. Thus the influence of these three variables other than giving a greater influence on employee performance among other infrastructure. Value of the correlation coefficient (r) indicates the magnitude of the relationship between each of the variables that variable workability (X1), labor discipline (X2) and motivation (X3) on employee performance (Y). calculation of the coefficient of partial determination r2 indicate that variable labor discipline (X2) has the greatest influence on the fluctuation of the performance of employees is equal to 44.1%.